Evaluating the reliability and validity of the Turkish version of the Parents’ Perceptions of Uncertainty Scale (PPUS-TR) - Melike Ayça Ay Kaatsız; Simay Ezgi Budak (The Turkish Journal of Pediatrics)
Background: The disease process can negatively affect both children and their parents, causing them to experience uncertainty. This study aims to determine whether the Turkish version of the Parents’ Perceptions of Uncertainty Scale (PPUS) is a valid and reliable instrument for measuring Turkish parents’ perceptions of uncertainty.